Access to Justice: Challenges and Opportunities for Lawyers in Serving Underrepresented Communities - Akhmad Indra Pranata; Rifqi Fadhli Ramadhan; Juan Fellix Ericson; Khairul fadlan lubis (Progressive Law Review, 2024)
Access to justice remains a critical issue, especially for underrepresented communities facing significant legal service barriers. Lawyers play a vital role in bridging this gap, yet they encounter numerous challenges, such as financial constraints, systemic biases, and limited resources. This paper explores the obstacles and opportunities for legal practitioners to serve marginalized groups. It highlights innovative strategies, including pro bono work, community legal clinics, and the use of technology to make legal services more accessible. The discussion emphasizes the need for systemic reforms and collaborative efforts to create a more equitable legal landscape.